IN-VIVO AUTOFLUORESCENCE SPECTROSCOPY IN ORAL CANCER DIAGNOSIS: A SYSTEMATIC - Dr.V.JAYANTH KUMAR MDS; Dr.T.N.UMA MAHESWARI MDS (International Journal of Pharma and Bio Sciences, 2014)
Oral cancer remains a major health problem in South and South East Asian countries. Despite the therapeutic advancements, the 5 year disease free survival rate has been around 50% only. The main problems associated with poor prognosis are late diagnosis of cancer and recurrence of the cancer. This systematic review aims in the assessment of the reliability of autofluorescence spectroscopy in oral cancer diagnosis. Autofluorescence spectroscopy is a non-invasive diagnostic tool. It can assess the molecular level changes which affect the optical properties of tissues. In this review a total of 9 studies have been assessed for their diagnostic accuracy. The review shows that porphyrin as a fluorophore has a good potential in diagnosis of oral cancer.